The Implementation of Differentiated Instruction Lesson Plan In The Practice of Teaching English For Adult Learners (TEAL) Course - Mujib Abdillah; Rudi Hartono; Sri Wuli Fitriati (English Education Journal, 2022)
Teaching preparation plays a vital role in teaching as the preparation which describes the elements will be used in teaching. It provides the basis for instructional focus and content. This research is aimed to describe the implementation of Differentiated Instruction Lesson Plan for Junior High School Students in The Practice of Teaching English For Adult Learners (Teal) Course In The Second Half Of 2021 At Satya Wacana Christian University. This study was described from the perspective of qualitative research which employ a case study design which observed which focuses on analysing and describing the development of lesson plan, implementing lesson plan, Differentiated Instruction, and the practice of teaching in compatible Kurikulum Merdeka for Junior High School students in The Practice of TEAL course. The subject of this study were 8 student-teachers joining the Practice of TEAL course (microteaching) in the second half of 2021 at Satya Wacana Christian University, Salatiga who participated in the research. Whereas, the object of this study was the teacher –trainees designing a Differentiated Instruction lesson plan for Junior High School students and its implementation in the Practice of TEAL course. To collect the data, the researcher used questionnaires, written interview, and classroom observation and all of the items were analysed qualitatively using content analysis. The result of this research showed that first, teacher-trainees had fulfilled all the elements in designing the lesson plan (identity, Objective of Learning, Learning Material, Learning Activity, Selection of Media, Selection of Learning Source, and Evaluation). Secondly, teacher-trainees had made the differentiation of learning visible in their teaching, in terms of readiness, learning profile, and interest. In addition, the researcher found out that most teacher-trainees had made progress in the most frequently occurring weaknesses from the first teaching to the next four but however they found most difficulty in formulating the objective of the learning. Lastly, the research described the effectiveness of Differentiated Instruction Lesson Plan since it facilitated supportive learning for heterogeneous learners. implementing lesson plan, Differentiated Instruction, and the practice of teaching in compatible Kurikulum Merdeka for Junior High School students in The Practice of TEAL course. The subject of this study were 8 student-teachers joining the Practice of TEAL course (microteaching) in the second half of 2021 at Satya Wacana Christian University, Salatiga who participated in the research. Whereas, the object of this study was the teacher –trainees designing a Differentiated Instruction lesson plan for Junior High School students and its implementation in the Practice of TEAL course. To collect the data, the researcher used questionnaires, written interview, and classroom observation and all of the items were analysed qualitatively using content analysis. The result of this research showed that first, teacher-trainees had fulfilled all the elements in designing the lesson plan (identity, Objective of Learning, Learning Material, Learning Activity, Selection of Media, Selection of Learning Source, and Evaluation). Secondly, teacher-trainees had made the differentiation of learning visible in their teaching, in terms of readiness, learning profile, and interest. In addition, the researcher found out that most teacher-trainees had made progress in the most frequently occurring weaknesses from the first teaching to the next four but however they found most difficulty in formulating the objective of the learning. Lastly, the research described the effectiveness of Differentiated Instruction Lesson Plan since it facilitated supportive learning for heterogeneous learners.